Hibridisasi Gaya Arsitektur Bangunan Pemerintahan di Rokan Hilir Masa Bupati Periode 2001-2021 - Miftahul Karima; Iwan Sudradjat; Indah Widiastuti (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2023)
Title: Hybridization of Architectural Styles in Government Buildings in Rokan Hilir during the Regents' Term from 2001-2021 The Architecture of Government buildings in Rokan Hilir Regency, Riau Province, Indonesia, demonstrates a change in style during the terms of three Regents who served between 2001 and 2021. The architectural style of government buildings initially referred to the Malay architectural style but later shifted orientation to architecture with various dome-shaped roofs. This article explains the changes in the architectural style of government buildings in Rokan Hilir from 2001 to 2021 and maps them genealogically. The research was conducted using a historical method, utilizing primary data from field observations and interviews and secondary data from development project archives and literature. The results of this research provide a genealogy of architectural styles in government office buildings in Rokan Hilir, regarding the Traditional, Modern, Dome, and Neo-Classical styles. Throughout their development, these four references underwent a process of hybridization, resulting in five hybrid styles as follows: Traditional-Neo-Classical Hybrid, Neo-Classical-Dome Hybrid, Traditional-Dome Hybrid, Dome-Modern Hybrid, and Traditional-Neo-Classical-Dome Hybrid.